THE STATE OF IMMUNE SYSTEM IN OLD-AGED PATIENTS WITH CHRONIC GENERALIZED PERIODONTITIS AND CORONARY HEART DISEASE - L. P. Malezhic; M. C. Malezhic; Y. I. Pinelis (Acta Biomedica Scientifica, 2012)
Chronic generalized periodontitis in the old-aged patients with coronary heart disease is accompanied by an imbalance in the content of some components of complement, hyperproduction s.IgA, IgG, IgM, elevated concentration of IL-8, IL-1α and low content of IL-4, high levels of the antibodies to HSP-70 in saliva and blood. Local anti-inflammatory therapy of chronic periodontitis does not restore normal immunity status. These data are pathogenic substantiation of the including immunocorrective therapies in to conventional treatment at periodontitis.